A Verbal and Non-Verbal Signs of Walt Disney Posters - Simarmata, Yustina Juita; Suastini, Ni Wayan; Eka Pratiwi, Desak Putu (Humanis; Vol 26 No 2 (2022)DO - 10.24843/JH.2022.v26.i02.p02, 2022)
This study aims to find out the verbal and non-verbal signs found in Walt Disney posters and analyze the meaning of verbal and non-verbal signs found in Walt Disney posters. Verbal sign is about text or words that appear in the Walt Disney poster. For the non-verbal signs appears as characters and colors used. The data of the research were downloaded from the pinterest. This study  used a descriptive qualitative method. This study used a theory by Saussure in Chandler (2007) to analyze verbal and non-verbal signs. While the theory from Barthes (1977) to analyze the meaning of signs, and the supporting theory from Cerrato (2012) to analyze color terms. This research reveals that 6 verbal signs and 6 non-verbal signs were found in Walt Disney posters. These signs also contained 5 denotative and 9 connotative meanings from the story line in the poster. These meanings were found in the words and picture of Walt Disney posters.